Optimal pricing and remanufacturing mode in a closed-loop supply chain of WEEE under government fund policy. (January 2021) - Zhang, Xue-mei; Li, Qian-wen; Liu, Zhi; Chang, Ching-Ter
Highlights: A closed-loop supply chain (CLSC) of WEEE is considered. Four dynamic game models are found to analyze the CLSC. Without government fund policy, the manufacturer remanufacturing mode is the better one. Under the government fund policy, the retailer remanufacturing mode is the best choice. Abstract: This paper investigates a closed-loop supply chain (CLSC) of WEEE consisting of a manufacturer, a retailer and a third party recycler, where the manufacturer can remanufacture used WEEE products or the manufacturer also can authorize the retailer to remanufacture used WEEE products. Combining the remanufacturing mode and government fund policy, four dynamic game models are found to analyze the effect of government fund policy on decisions of CLSC. In addtion, this study investigate the effect of government fund policy on consumer, environment and society using numerical analysis. The results show that: Without government fund policy, the manufacturer remanufacturing mode is better for CLSC members. By contrast, under the government fund policy, the retailer remanufacturing mode is the best choice. When government fund policy parameters meet a certain range, it can increase supply chain members' profits and promote the recycling and remanufacturing of used WEEE products. The changing trends of supply chain members, consumer surplus, environmental impact and social welfare are the same, only the change thresholds of government fund policy parameters are quite different. When the government sets appropriate fund policy parameters, government fund policy is benefit for supply chain members, consumer, environment and society.